Sanksi Pidana Terhadap Pelaku Perusakan Hutan dalam Undang-Undang Nomor 32 Tahun 2024 Perspektif Hukum Pidana Islam - Windi Aimar Noersy; Ali Khosim; Yayan M Royani (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Kamojang Nature Reserve is one of the vital conservation areas in West Java that faces serious threats due to land-use conversion, geothermal exploration, illegal tourism activities, and weak legal supervision. This study aims to: (1) examine the background of forest destruction crimes in the Kamojang Nature Reserve area; (2) analyze the resulting ecological and social impacts; and (3) assess the legal sanctions imposed on perpetrators based on Law Number 32 of 2024 concerning the Conservation of Biological Natural Resources and Their Ecosystems, as well as from the perspective of Islamic criminal law. The research employs a normative juridical approach with data collected through literature study. The data used is qualitative in nature, derived from secondary sources such as statutory regulations, Islamic criminal law literature, scientific journals, and previous research, as well as tertiary sources including legal dictionaries, encyclopedias, and language dictionaries. This study adopts three theoretical frameworks: the Theory of Penalization, which explains the basis and objectives of criminal sanctions in positive law; the Theory of Jarimah, which classifies criminal acts in Islamic law; and the Theory of Maqasid al-Shari‘ah, which emphasizes the importance of environmental protection as an integral part of public welfare (maslahah). The findings indicate that economic motives, weak law enforcement, and low public awareness are the main causes of forest destruction. The impacts include the loss of wildlife habitats, disruption of water cycles, increased ecological disasters, and a decline in community well-being. Under positive law, perpetrators are subject to imprisonment and fines, while under Islamic criminal law, such acts fall under the category of jarīmah taʿzīr, which entails sanctions that are educational, preventive, and restorative in nature. This study underscores the importance of synergy between state regulations and Islamic legal values in preserving ecosystem sustainability and achieving ecological justice.